A relação entre comércio e instituições republicanas em Maquiavel - Fontes, Igor Ferreira (2020)
This research aims to investigate, within Machiavelli’s work, how the institutions of the Republic would shelter commerce and how the former could be useful to it. The research develops from the following problem: how does commerce is inserted into the Republican project elaborated by Machiavelli for Florence? The hypothesis to be verified is that commerce can contribute to wealth accumulation, population increase and territorial expansion of the republic, and that the expansion of institutions to host all the humors of the city tends to hinder the interference of the great in the commerce exercised by other citizens, which would provide more favorable conditions to the performance of such activity. The methodology to be used is Skinner's contextualism. To carry out the research, three specific objectives were determined, corresponding to the three chapters of the dissertation: 1) to contradict the judgments of Savonarola and Machiavelli about the supposed relationship between commerce, mercenary weapons and corruption; 2) check how commerce can be useful to the republic; and 3) to analyze how the composition of the republican institutions thought by Machiavelli in the Discursus florentinarum rerum post mortem iunioris Laurentii Medices would be reflected in the government's decisions regarding commerce. The conclusion reached is that Machiavelli admits the possibility of commerce coexisting with the vivere libero and being exercised in order to contribute to the growth of the republic in wealth and domains and elaborates for Florence a political-institutional structure that requires agreement between the great and the people to deliberate an issue, which allows the latter to institutionally owe any attempt by those to command the economic life of the republic.